Preventive Effects against Retinal Degeneration by Centella asiatica Extract (CA-HE50) and Asiaticoside through Apoptosis Suppression by the Nrf2/HO-1 Signaling Pathway - Dae-Won Park; Yeong-Geun Lee; Yong-Joon Jeong; Hyelin Jeon; Se-Chan Kang (MDPI AG, 2021)
Age-related macular degeneration (AMD) is caused by the chronic and gradual oxidative degeneration of the retina. Unfortunately, the general purpose of current treatments is to slow AMD progression, as the retina cannot be restored to its pre-AMD condition. We aimed to identify natural products that can be potential treatments that prevent AMD and can delay the development of late-AMD and selected Centella asiatica extract (CA-HE50), which shows excellent efficacy in cytoprotection. In animal experiments using N-methyl-N-nitrosourea (MNU), CA-HE50 dramatically increased the thickness of photoreceptors and the outer nuclear layer (ONL) and the number of nuclei in the ONL (p < 0.05). Using retinal epithelial ARPE-19 cells showed that CA-HE50 inhibited apoptosis through inhibition of the intrinsic apoptosis signaling pathway and cell cycle regulation (p < 0.05). The anti-apoptotic efficacy was confirmed to be due to activation of the Nrf2/HO-1 antioxidation pathway (p < 0.05). These results were also observed with asiaticoside, a functional substance of CA-HE50. In addition, the accumulation of oxidized-N-retinylidene-N-retinylethanolamine (A2E), which induces AMD, was inhibited by CA-HE50, resulting in increased ARPE-19 cell viability (p < 0.05). This study demonstrates that CA-HE50 is worth further research and human application tests, to develop it as a raw material for treatment or dietary supplement for the prevention of AMD.